Esclarecimento, moral e religião: a possibilidade de uma religião moral no pensamento kantiano. - COSTA, Mickael dos Santos (2021)
This dissertation aims to understand the possibility of a moral religion in the thought of Immanuel Kant. This is a bibliographic research developed in an interdisciplinary perspective relating religion, philosophy and morals. For this purpose, in a first moment, the situation of religion, more specifically the Christian religion, is contextualized with the advent of modernity, highlighting elements such as: the Protestant Reformation, Lutheran Orthodoxy and Pietism in Germany of the centuries. XVII and XVIII. Then, Kant's objections to the scientific pretensions of dogmatic metaphysics and, more closely, to rational theology, developed in the Critique of Pure Reason, are presented, emphasizing his warnings about the danger of retreating to explanations based on transcendent, such as: the accommodation of reason. In the sequence, the referred accommodation is articulated to the menority, fought by Kant in the text about the Enlightenment, analyzing, above all, his objection to religion, as a guardianship instrument, as well as the possibilities of an enlightened religion. Finally, the relationship between morality and religion is described and how it must this be preceded by a moral, which is based on the autonomy of the will linked to the idea of freedom. It is explained, in the light of the Critique of practical reason and Religion within the limits of simple reason, that the essence of religion for Kant is morality and that even the religion of petition (statutory), being purified in its concepts and practices, can serve as a means for a pure religious faith, realizable in the form of a church or ethical community, in which the people autonomously submit to moral laws, the concept of God in this being only the idea of a moral legislator.